Prevalence of obesity in paediatric psoriasis and its impact on disease severity and progression - SALMAN, ANDAÇ; SEÇKİN GENÇOSMANOĞLU, DİLEK; AYDINER, ELİF; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2017)
Background/Objectives: The current literature suggests there is a possible connection between paediatric psoriasis and obesity. However, there is a paucity of research on the influence of increased adiposity on the severity of paediatric psoriasis and disease progression. We aimed to compare the prevalence of being overweight or obese in paediatric psoriasis patients and controls and assess the potential impact of being overweight/obese on disease severity and progression of disease. Methods: This multicentre prospective case-control study included 289 psoriasis patients (aged < 18 years) treated and followed up by one of the four university hospitals in Turkey. The control group consisted of 151 consecutive age-matched and sex-matched children who lacked a personal or family history of psoriasis. The participants' characteristics, psoriasis-related parametres (e.g., initial subtype, psoriasis area and severity index, presence of psoriatic arthritis) and body mass index were determined. Results: The difference between the prevalence of being overweight/obese among psoriatics (28%) and the control group (19%) was significant (P = 0.024). Being overweight/obese had no significant impact on disease severity and unresponsiveness to topical treatment. Within a median follow-up time of 12 months, 23% of our patients with localised disease at disease onset progressed to generalised disease. The impact of being overweight/obese on disease progression was found to be non-significant; however, disease duration was found to have a significant impact on disease progression (P = 0.026). Conclusions: Although it is not associated with disease severity and course, increased bodyweight may be a health problem for psoriatic children.
Keywords: disease progression; disease severity; obesity; paediatric psoriasis; METABOLIC SYNDROME; GUTTATE PSORIASIS; CHILDREN; ASSOCIATION; COMORBIDITIES; EPIDEMIOLOGY; METAANALYSIS; ADOLESCENTS; MANAGEMENT; OVERWEIGHT